Environmental Science - Chiras, Daniel D (Burlington : Jones & bartlett learning, 2013)
Updated throughout with the latest data from the field, the new Ninth Edition of Environmental Science provides a comprehensive, student-friendly introduction to the environmental issues facing society today and offers numerous solutions for how we can create a more sustainable way of life. Chiras focuses on the underlying cause of environmental problems and is sure to present both sides of the issue at hand. Each chapter highlights critical analysis to help student determine how to approach these complex topics and determine the merits of the debates for themselves. The Ninth Edition includes updated and expanded coverage of environmental economics, ecology, and the application of science and technology as it applies to environmental concerns. - Updated and revised throughout to keep pace with the changes in the field. - New and updated Go Green marginal notes provide helpful, inexpensive, and practical tips which will help us all build a sustainable future. - Chapter 15, Foundations of a Sustainable Energy System, includes new content on energy-conservation options, fuel efficiency standards, electric cars, and 'green buildings'. - Stresses critical thinking skills by urging students to analyze complex issues and make rational decisions on key topics.
Includes Include references
Keywords: Biology; Environmental science; Environmental Biology